The princess and the pea - Andersen ; Hans Christian (London Mind to Mind, 2010)
The tale follows a young princess who is tested for her true royalty by being asked to sleep on a stack of mattresses with a single pea placed underneath. Despite the luxurious bedding, she is unable to sleep due to the discomfort caused by the tiny pea, proving her sensitivity and authenticity as a genuine princess. This charming edition features colorful illustrations and clear text, bringing Andersen$1 (Bs classic fairy tale to life in an engaging and accessible way.s